Particle Accumulation in Microchannel and Its Reduction by Surface Acoustic Wave (SAW) - Sriphutkiat, Yannapol (2016)
Printing highly viscous ink through small nozzle(s) is limited because of the clogging problem. Particle accumulation along the nozzle wall makes the channel gradually narrower and finally obstructs the upstream flow. In order to understand this phenomenon the accumulation of micro-particles in a 100- m microfluidic channel was observed under a microscope. Concentration of sodium alginate and micro-particles, flow rate were varied, and the accumulation rate was used to characterize the clogging problem. It is found that increasing the particle concentration and decreasing the flow rate would expedite the accumulation rate. At the flow rate of 10 l/min and particle concentration of 1% and 1.4% the accumulation rate was 2.8 and 3.1 %/min, respectively. The corresponding values decreased to 0.006 and 0.010 min-1 at the flow rate of 2 l/min. Increasing the particle concentration from 0.2%, 0.6%, 1.0% to 1.4% shows gradual increase of accumulation rate from 1.5, 2.1, 2.8 to 3.1 %/min, respectively. With 1% micro-particles and 1%, 3% and 5% alginate the accumulation rate was 4.6, 5.9 and 4.1 %/min, respectively. However, above 4% alginate concentration, the micro-particles would agglomerate into a bridge structure for partial obstruction. In order to reduce the particle accumulation, the standing SAW was generated in the microfluidic channel using a pair of interdigitated transducer (IDT) at the optimum frequency and power to move the accumulated particles away from the wall and, therefore, reduce the chance of clogging. The accumulation rate dropped from 3.14 %/min to 0.21 %/min at the flow rate of 2 l/min and 1.4% particle in water. In summary, the dependence of particle accumulation on the hydrodynamic parameters was found. Applying standing SAW could effectively reduce the particle accumulation, which may enhance the accuracy and reliability in 3D printing.